2012
DOI: 10.1016/j.jacc.2012.08.119
|View full text |Cite
|
Sign up to set email alerts
|

TCT-103 The Transaortic Approach for Transcatheter Aortic Valve Replacement: Initial Clinical Experience in the United States

Abstract: CE Mark approval in September 2011 and to date over 100 commercial implants have been performed. The device is composed of a porcine biologic valve attached to a self-expanding nitinol stent designed for simple 2-step implantation and characterized by controlled positioning, self-seating in the native annulus resulting in a negligible paravalvular leak rate. The device was tested in patients at high-risk for mortality with open surgical repair. Methods: Ninety (90) patients (femaleϭ69%) with severe aortic sten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
64
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(71 citation statements)
references
References 0 publications
6
64
1
Order By: Relevance
“…Finally, there appears to be a shorter learning curve with the transaortic approach than the transapical approach, thus exposing fewer patients to excess risk during the introduction of the technique [21]. Despite these potential advantages, our review failed to show that the transaortic approach is superior to the transapical approach in most outcomes and this requires further discussion.…”
Section: Commentmentioning
confidence: 81%
“…Finally, there appears to be a shorter learning curve with the transaortic approach than the transapical approach, thus exposing fewer patients to excess risk during the introduction of the technique [21]. Despite these potential advantages, our review failed to show that the transaortic approach is superior to the transapical approach in most outcomes and this requires further discussion.…”
Section: Commentmentioning
confidence: 81%
“…Bapat and colleagues [15] examined TAVR by TA and TAo approaches and reported no significant difference in 30-day mortality (7.7% for 91 patients undergoing TA TAVR and 11.8% for 17 patients undergoing TAo TAVR; p ¼ 0.577). In their comparison of 44 patients undergoing TAVR through TAo access against 76 patients undergoing TAVR through a TA route, Lardizabal and colleagues [16] reported a 30-day all-cause death rate of 14% and 14% for TAo and TA, respectively. Other studies have reported 30-day mortality for TA TAVR ranging from 5.7% to 17.5% [17][18][19][20].…”
Section: Commentmentioning
confidence: 99%
“…Nonetheless, for transaxillary TAVR, the 30-day all-cause mortality rates were 8.6 % and 4.2 % ( p = 0.25), the 30-day major stroke rates were 8.6 % and 3.9 %, and the MACCE rates at 30 days were 14.3 % and 12.1 % ( p = 0.67) for the Pivotal study and continued access patients, respectively. Lardizabal et al [ 8 ] reported on 44 consecutive patients undergoing TAo-TAVR with the Edwards SAPIEN valve and compared them to 76 consecutive patients undergoing TA-TAVR. They found that the rate of device success was similar at 89 % for the TAo-TAVR group and 84 % for the TA-TAVR group ( p = 0.59) with no difference in signifi cant paravalvular regurgitation .…”
Section: Discussionmentioning
confidence: 99%